Sistem Pasar Output Pendidikan Islam - Muhammad Anggung Manumanoso Prasetyo (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
Social economic reality forced the Moslem population to be more concerned with general education so get rid of the religious education forward. A common problem that describe into two, the first in the case of a majority Muslim country the government does not understand that the core of nation-building through education is human development itself as a means and purpose. The second, in the case of a minority Moslem country the problem was faced is protective government policy until the movement of Islamic educational institutions in innovating was limited. This articles elaborates the illustration how education development to the right direction must beginning with a system approach in the education sector adjusted the need of the global market. Basically, every system created to handle something that routinely happens. Systems approach is a philosophy about the structure that coordinates activities in an organization with the most excellent way. The data collected for several books and journal which provided to the illustrations. The conclusion, there are three domain strategies and education policies for the government to develop education system effectiveness, are defense and security, productive workforce, positive social output. Especially for education institution, the strategy is (1) selection and development of graduate products; (2) financial education effectiveness for competitive advantage; (3) developing human capital; (4) moving, caring, and innovating; (5) marketing strategy; and (6) alliance strategy, building a network with synergy.